Recognizing soft templates as stimulators in multivariate modulation of tin phosphate and its application in catalysis for alkyl levulinate synthesis. Issue 1 (12th November 2020) - Manjunathan, Pandian; Shanbhag, Dhanush Y.; Vinu, Ajayan; Shanbhag, Ganapati V.
Abstract : Soft template tunes and controls explicitly both morphology and nature of active sites during the synthesis of tin phosphate catalyst. This synthesis strategy helped in producing alkyl levulinate in high yields from one-pot alcoholysis of furfuryl alcohol. Abstract : Catalyst synthesis is an art where an inefficient material can be remarkably converted into a highly active and selective catalyst by adopting a suitable synthetic strategy to tune its properties during synthesis. The underlying principle of the strategy presented here is the integration of tailoring the structural and chemical behavior of tin phosphates with tuned catalytic active centers directed by employing different structure directing agents (SDAs) and the attempt to understand this in detail. It is demonstrated how soft templates can be effectively used for their so far unknown utilization of tuning the active sites in phosphate containing catalysts. We found that, by using an appropriate synthesis strategy, it is possible to tune and control explicitly both the catalyst morphology and the nature of active sites at the same time. The 31 P MAS NMR study revealed that employing SDAs in the synthesis strongly influenced the nature and amount of phosphate species in addition to porosity. The resultant different nanostructured SnPO catalysts were investigated for one-pot synthesis of alkyl levulinates via alcoholysis of furfuryl alcohol. Among the catalysts, SnPO-P123 exhibited greater butyl levulinate yield via alcoholysis of furfuryl alcohol with n -butanol and the study was extended to synthesize different alkyl levulinates. Importantly, the active sites in the SnPO-P123 catalyst responsible for the reaction were elucidated by a study using 2, 6-lutidine as a basic probe molecule. This study therefore provides an avenue for rational design and construction of highly efficient and robust nanostructured SnPO catalysts to produce alkyl levulinates selectively.